ANALISIS YURIDIS PENETAPAN PERKAWINAN BEDA AGAMA ANTARA KEVIN SANGIAN HENDRIK RUMIAP DENGAN NUR REZKI ANGGRAENI AKHBAR MENURUT HUKUM PERKAWINAN YANG BERLAKU DI INDONESIA (STUDI PENETAPAN PENGADILAN NEGERI MAKASSAR NOMOR 622/PDT.P/2018/PN.MKS) - Praditya Arrahim Pahlevi; Muriani Muriani (Reformasi Hukum Trisakti, 2021)
Interfaith marriage exists between Kevin Sangian Hendrik Rumiap and Nur Reski Anggraeni Akhbar. The issue is whether interfaith marriage is allowed under Indonesian marriage law that is in force, and if the provision of Number 622/Pdt.P/2018/PN.Mks that authorizes interfaith marriage complies with that law. The normative legal research method uses secondary data and is descriptive in character. analysis of qualitative data. Conclusion by deductive result. The findings of the study, discussion, and conclusion show that interfaith marriage agreements are strictly regulated in the Compilation of Islamic Law (in Article 40 letter (c) and Article 44, which states that every man is forbidden from marrying a woman who is not Muslim, and every woman is forbidden from marrying a man who is not Muslim. The District Court's decision to allow interfaith marriages, District Court No. 622/Pdt.P/2018/PN.Mks, does not follow the Compilation of Islamic Law or Law No. 1 of 1974, but rather Article 2 paragraph (2) of Government Regulation No. 9 of 1975 and Supreme Court Decision Number 1400K/Pdt/1986.